Parish Records and the History of Philippine Epidemics - Xenos, Peter (2020)
The Philippine epidemic experience suggests a research perspective that is attentive to local spatial variation and also recognizes connections across long periods of time, particularly across the Spanish and American colonial eras and the epidemic experience then and since. Among historical materials that need to be incorporated into the discourse and connected with evidence from modern, spatially disaggregated data systems are parish archival records of births, deaths, and marriages; households; and population changes. This research note outlines the Philippine parish records and presents illustrative results from twenty-eight parishes. Those records include local time series of deaths from which mortality crises, generally reflecting epidemics, are presented.
Keywords: Epidemics; Epidemics--History; Demography; Mortality